CREDO-MIX - DIGITAL MODEL PROJECT - Белятинський, А. О.; Чичикало, Л. Г.; Резнік, О. М (Science-based technologies, 2009)
System CREDO-MIX which is intended for the decision of problems of designing of general plans of the enterprises, transport constructions, inhabited and civil objects is considered.